Industry-Based Curriculum and Graduate Employability: An Effort to Reduce Intellectual Unemployment - Rasmawar Rasmawar; R. Madhakomala; Linda Ika Mayasari (Eastasouth Institute, 2026)
Intellectual unemployment is a major challenge in the modern education system due to the increasing mismatch between graduate competencies and the needs of the workforce. The transformation of the digital economy, the development of artificial intelligence (AI), and the Industrial Revolution 4.0 require educational institutions to produce graduates who are not only academically superior but also adaptable to technological changes and global industrial needs. However, the Indonesian education system still faces a skills mismatch problem due to a curriculum that tends to be theoretical, less responsive to industrial developments, and has not fully integrated 21st-century skills. This study aims to analyze the role of an industry-based curriculum in improving graduates' job readiness as an effort to reduce intellectual unemployment, while also examining the transformation of the curriculum from a Critical Discourse Analysis (CDA) perspective. The study uses a qualitative approach with literature study and critical discourse analysis methods. Data were obtained from reputable international journals indexed by Scopus, accredited national journals, reports from international institutions, and education and employment policy documents. The results show that an industry-based curriculum can improve graduate employability through strengthening project-based learning, industrial internships, digital literacy, and soft skills development. The implementation of the link and match program and the Independent Learning and Independent Campus (MBKM) program also contribute to improving graduates' job readiness. However, from a CDA perspective, the transformation of the industry-based curriculum demonstrates the dominance of economic logic and neoliberalism in education, which directs education as an instrument for providing labor for industry. Therefore, the development of an industry-based curriculum needs to be carried out in a balanced manner so that education is not only oriented towards job market needs but also maintains its humanistic function in developing critical, creative, and socially conscious individuals.